Is self-perception of oral health associated with expectations of employability? - Luciana Raquel D'ERAMO; Noemi Emma BORDONI; Lourdes COTELO; Marìa Belen PEREZ; Marìa Laura SÁNCHEZ; Pablo Andres SALGADO; Eugenio BELTRAN-AGUILAR; Aldo Fabián SQUASSI (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this study was to develop and validate a questionnaire that allows a systematic evaluation of the impact of self-perceived oral health on expectations of getting a job on adult population seeking dental care, and to describe its associations with demographic characteristics, job related, and health coverage variables. We designed a descriptive cross-sectional study including men and women aged 18 to 65 years from a population seeking dental services in a walk-in clinic. In a first stage we design and validated an instrument on a sample of 100 subjects. The questionnaire was registered in a Likert scale, with higher scores represented higher impact of the oral status self-perception on employability. We calculated internal consistency, construct validity, and domains validation. The final instrument consisted in an 18-item questionnaire (Cronbach α = 0.814), grouped into two domains based on exploratory and confirmatory factor analysis. The total variance explained with values >1 was 66 percent, grouping questions into six components. One domain refers to oral health status and importance of dental aesthetics, while the other refers to specific job-seeking elements. In a second stage we applied the questionnaire on 800 participants from the same population of reference. Women, people who intended to change jobs, those younger than 40 years old, having health insurance, and higher educational level showed statistically significant higher scores than their counterparts (p<0.001). We developed a tool that enables evaluating the impact of self-perceived oral health on expectations of getting a job for adults seeking emergency care in a dental clinic.